Schiller and the task of the illustrated intelligentsia in face of transcendental criticism - Bezerra, Ralphe Alves (Argumentos - Revista de Filosofia, 2019)
Taking as a reference the methodological challenge faced by Schiller, this article discusses the idea that the Philosophy of Illustration (idealism, classicism and romanticism) represents the effort of the German intelligentsia to carry out a task imposed by Kritik der reinen Vernunft [1787] by Kant. In this sense, Schiller tries, against the transcendental limits of Kritik der Urteilskraft [1790], to find the principle of objectivity of beauty. Indeed, through his aesthetic political project, Schiller, by means of the beauty, intends to promote the synthesis between the rational and sensible forces of the being, for, only this way, he believes, indeed one can effect the full anthropological development and the true men‘s political freedom of the men.